Some worrying theoretical consequences of the non-linear relationship between the economic size of preferential trade agreements and welfare (2004)
This paper demonstrates that in the standard Viner-Lipsey customs unions analysis, there is a non-linear relationship between welfare and the economic size of preferential trade agreements. It is concluded that signing preferential trade agreements with countries that have a large trade potential is likely to improve welfare, but that a minimum economic size threshold may be required for such outcome. Otherwise, preferential trade agreements may reduce welfare. The paper also demonstrates that within that framework, the lower the trade barriers towards non-member countries, the greater the economic size that may be required for preferential trade agreements to be welfare improving. This theoretical paper suggests that if small countries follow preferential trade agreement strategies such as those applied by the European Union, and more recently by the United States, Mexico and Chile, they should do so with care, clear objectives and national commitment.